Some New Delay Integral Inequalities in Two Independent Variables on Time Scales - Bin Zheng; Yaoming Zhang; Qinghua Feng (Journal of Applied Mathematics)
Some new Gronwall-Bellman-type delay integral inequalities in two independent variables on time scales are established, which can be used as a handy tool in the research of boundedness of solutions of delay dynamic equations on time scales. Some of the established results are 2D extensions of several known results in the literature, while some results unify existing continuous and discrete analysis.